(untitled) (Journal of Hama University, 2024)
This study aimed to identify basic education teachers’ awareness of the digital skills of the twenty-first century teacher (infographic technology). The study sample consisted of (171) basic education teachers, both male and female. To achieve the goal of the study, a questionnaire was designed that consisted of (31) items. The descriptive analytical method was used. After applying the study tools and analyzing the data, the results showed the following: - The level of teachers’ awareness of the importance of infographics and its uses in education is low, and the general average reached (1.87). The average importance axis was (2.12), while the average axis of uses of infographics in education was (1.63). -There are a number of challenges that limit teachers’ use of infographics in education, the most notable of which are poor computer and Internet usage skills, and lack of training in using infographics. - There are no statistically significant differences between the average scores of teachers in their level of awareness of the importance of infographics and its uses in education due to the variable number of years of experience. - There are statistically significant differences between the average scores of teachers in their level of awareness of the importance of infographics and their uses in education due to the academic qualification variable in favor of teachers with an academic qualification (postgraduate studies). - There are no statistically significant differences between the average scores of teachers in their level of awareness of the importance of infographics and their uses in education due to the educational stage variable (first cycle, second cycle).